Giant functional parathyroid carcinoma: a case report and literature review - Wu, Jian; Sun, Yifang; Zhang, Qian; Lin, Ying; Wang, Pengzhen; Leng, Lei; Cao, Lei; Yu, Feng; Deng, Haiyan (Frontiers in Oncology, 2024)
Background: Parathyroid carcinoma is an infrequent neoplasm of the endocrine system, constituting roughly 0.5% to 5% of cases of primary hyperparathyroidism.The diagnosis of this condition presents a unique challenge for healthcare professionals.Case Report: We present a case of a 77-year-old female patient who presented with a longstanding right-sided neck tumor. The Positron emission tomography-computed tomography (PET-CT) scan detected a substantial tumor situated at the inferior border of the thyroid gland. A surgical procedure was conducted, resulting in the total excision of the tumor. The diagnosis of parathyroid carcinoma was confirmed through pathological investigation. At the six-month follow-up, the patient exhibited favorable post-operative outcomes with no evidence of recurrence.The primary approaches for managing parathyroid carcinoma involve precise diagnosis and surgical removal. This case report provides confirmation that the implementation of rigorous treatment measures can yield a substantial improvement in the prognosis.